Village Fund Management in Bulukumba Regency - Ismail, Ismail; Muhajir, Muhajir (Program Pascasarjana Universitas Negeri Makassar, 2024)
One of the most important things from the birth of Law Number 3 of 2024 concerning the Second Amendment to Law Number 6 of 2014 concerning Villages, namely rearranging the position, administration of government, principles and objectives of village regulation. One of the important points in this law is the existence of special rules regarding village funds. Nationally, the average per village has received Rp. 1.5 billion to 2 billion per village, including 109 villages in Bulukumba Regency, South Sulawesi, so that its use can reduce poverty rates and improve the welfare of people in villages. This study aims to examine and describe the management of village funds in realizing independent villages in Bulukumba Regency. This study uses a qualitative approach in the form of a case study to obtain a comprehensive explanation related to the leadership of the village head, related organizations, programs funded by village funds, and the social situation of the community after the existence of the village funds that are researched, and studied in depth. This research is expected to provide benefits both for the development of science in the field of public administration, as well as as as used as a policy basis to assist village governments in managing village funds in order to realize an independent village in Bulukumba Regency.